Start-up and operation of novel EN-MBBR system for sidestreams treatment and sensitivity analysis modeling using GPS-X simulation - Ahmed M. Faris; Haider M. Zwain; Majid Hosseinzadeh; Hasan Sh. Majdi; Seyed Mostafa Siadatmousavi (Alexandria Engineering Journal, 2022)
Worldwide, most treatment systems are retuning sidestreams to the wastewater treatment plant head without treatment. This study established an innovative process to separately treat all sidestream lines (supernatant gravity thickener, underflow mechanical thickener, and centrate) away from plant mainstream and return treated sidestream effluents to plant wastewater outfall instead of wastewater head. It aims to start up and operate a novel EN-MBBR to eliminate sidestreams impacts on a full-scale A2/O sewage treatment plant. The effects of DO, RAS, and media portion on the reactor were modeled using GPS-X. The system successfully started and reached a steady-state in 28 days. The pilot system processed 30 m3/d of the sidestreams, and the average of 8 months effluent concentrations for COD, BOD, TSS, PO4, NH4, NO2, NO3, H2S were 55, 4, 11, 0.16, 0.2, 0.17, 100, and 0.11 mg/L, respectively. Adding 3 kg/day of calcium hydroxide contributed to improving the nitrification process and reducing phosphates from 40 mg/L to 0.16 mg/L, but it caused an initial shock to the system that lasted more than a week, and then it was stabilized. Modeling results showed that DO concentrations affected the nitrification process but stabilized at a concentration of 3 mg/L. When operating the EN-MBBR as an EN-IFAS system, the RAS has positively contributed to reducing sludge in this system, whereas the sludge proportion is reduced by 60%. The media portion had a significant effect on the removal of nutrients, as it gave the best results when the rate of reactor filling with carriers was between 40 and 50%.